PENGABDIAN KEPADA MASYARAKAT DENGAN MEMBAGIKAN HANDSANITISER KEPADA PENGGUNA JALAN DAN JAMAAH MASJID PADA MASA COVID 19 - Daga, Rosnaeni; Salam, Karta Negara; Suwandaru, Rachman; Pratiwi Ar, Dhita; Sasmita, Halida; Panus, Panus; Ramlah, Ramlah; Fatwa, Nur (Yayasan Education and Social Center, 2025)
Covid-19 is a disease caused by a new type of corona virus, namely SARS-CoV-2. Covid-19 was first discovered in Wuhan City, China in December 2019 and was declared a pandemic by the World Health Organization (WHO) in March 2020. Covid Virus-19 can be spread by touching contaminated surfaces. One of the recommended preventive measures is adopting a clean lifestyle. The clean lifestyle that is applied is discipline in using hand sanitizer. One form of community service carried out by the Nitro Makassar Institute of Business and Finance Team is by distributing hand sanitizer to road users and mosque congregations. The distribution of hand sanitizers is a concrete form of preventing and breaking the chain of spread of Covid-19, especially in Makassar City. The hand sanitizer was obtained from the self-help of the service team. Hand sanitizer distribution is accompanied by education about the benefits and use of hand sanitizer. The activities carried out received a positive response from the community, especially road users and mosque congregations, they were very enthusiastic when hand sanitizer was distributed.